Pengaruh Motivasi Kerja, Modal Sosial, dan Disiplin Kerja terhadap Produktivitas Kerja - Mila Hariani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The company will always struggle to survive in the competition. Management will continue to look for ways to survive by developing the advantages it has compared to other companies. Management will also build the company from within to be ready to compete in the future. One of the developments carried out by management is a form of employee productivity development. Many factors that build employee productivity can be developed. This research was conducted to determine the impact of motivation, social capital, and work discipline on the formation of employee productivity. This research was conducted at a company in Sidoarjo. Data was obtained by distributing questionnaires to all employees which found 127 respondents. The study used multiple linear regression as the data analysis. The results obtained that work motivation plays a role in the formation of employee productivity. Furthermore, social capital also has a significant influence on the formation of employee productivity. The researcher also concludes about the importance of work discipline